Functional Analysis of the Unique Cytochrome P450 of the Liver Fluke Opisthorchis felineus. - Mariya Y Pakharukova; Valentin A Vavilin; Banchob Sripa; Thewarach Laha; Paul J Brindley; Viatcheslav A Mordvinov (Public Library of Science (PLoS), 2015)
The basic metabolic cytochrome P450 (CYP) system is essential for biotransformation of sterols and xenobiotics including drugs, for synthesis and degradation of signaling molecules in all living organisms. Most eukaryotes including free-living flatworms have numerous paralogues of the CYP gene encoding heme monooxygenases with specific substrate range. Notably, by contrast, the parasitic flatworms have only one CYP gene. The role of this enzyme in the physiology and biochemistry of helminths is not known. The flukes and tapeworms are the etiologic agents of major neglected tropical diseases of humanity. Three helminth infections (Opisthorchis viverrini, Clonorchis sinensis and Schistosoma haematobium) are considered by the International Agency for Research on Cancer (IARC) as definite causes of cancer. We focused our research on the human liver fluke Opisthorchis felineus, an emerging source of biliary tract disease including bile duct cancer in Russia and central Europe. The aims of this study were (i) to determine the significance of the CYP activity for the morphology and survival of the liver fluke, (ii) to assess CYP ability to metabolize xenobiotics, and (iii) to localize the CYP activity in O. felineus tissues. We observed high constitutive expression of CYP mRNA (Real-time PCR) in O. felineus. This enzyme metabolized xenobiotics selective for mammalian CYP2E1, CYP2B, CYP3A, but not CYP1A, as determined by liquid chromatography and imaging analyses. Tissue localization studies revealed the CYP activity in excretory channels, while suppression of CYP mRNA by RNA interference was accompanied by morphological changes of the excretory system and increased mortality rates of the worms. These results suggest that the CYP function is linked to worm metabolism and detoxification. The findings also suggest that the CYP enzyme is involved in vitally important processes in the organism of parasites and is a potential drug target.